(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This research article pays special attention to the ideal artistic degree of illumination in the educational ghazals of the poet Mirzo Kezhnabek, as well as important topics and questions about the perception of the world, its essence - the transience of the world, understanding and explaining its meaning and value, about trying not to succumb to it, its deception, about curbing passion that flows into love, as well as about self-knowledge and self-denial, about achieving the goal through this, about overcoming ignorance, awakening from inertia, ignorance, about accepting the status of a godly person. The poet’s educational ideas in these ghazals are explored in harmony with issues that are also important in Sufism, including linking them with the problem of the perfect person.